Medical nutrition therapy and vitamin D supplementation improved nutritional status and quality of life in relapse systemic lupus erythematosus patient : A case report - Ayu Diandra Sari; Yohannessa Wulandari; Diyah Eka Andayani (World Nutrition Journal, 2022)
Medical nutrition therapy (MNT) plays pivotal role in comprehensive management of autoimmune disease, includes systemic lupus erythematosus (SLE). Meanwhile, MNT for SLE is still not a concern in many international clinical practice guidelines. Many studies reported about nutritional declines and metabolic complications related to long term corticosteroid use in SLE patients, i.e. malnutrition, sarcopenia, hypovitaminosis D, hypertension and etc. Besides, obesity is more expected become important risk factor in SLE.